Winter survivorship of hatchling broad-snouted caimans (Caiman latirostris) in Argentina - Viotto, Evangelina del Valle (2022)
The first life stage of crocodilians is considered the most critical in terms of survival, particularly in regions that have well-defined cold seasons. To estimate this parameter for hatchling broad-snouted caimans, Class I (CI = snout-vent length < 25 cm), we released 36 caimans (18 in 2018, and 18 in 2019) born in captivity that were equipped with VHF radio-transmitters, and we monitored them during each first winter season. We actively searched for the animals during field trips and registered their status as alive, dead, lost transmitter (LT), or radio signal ceased (SC). Due to the occurrence of LT and SC, we proposed eight possible survival scenarios, assuming different combinations of "alive" and "dead" caimans. We analyzed each scenario and compared it between years. In 2018 we found 55.5% dead and 44.5% LT, resulting in survival estimates from 0 to 0.38 according to the scenario. In 2019 we found 50% alive, 33% LT, and 17% SC, with survival varying from 0.5 to 1. Survival in 2019 was higher than in 2018 in all scenarios. Assuming predation was the most plausible cause of LT, with the most likely scenarios estimated 0% survival in 2018 (although the minimum detectable by this methodology is 5%) and 67% in 2019. This information can be helpful for ranching with release programs, as it allows for a better adjustment of the reintroduction rate and opens up the possibility of earlier releases when resources to keep animals in enclosures are scarce